Anisotropic Collective Charge Excitations in Quasimetallic 2D Transition‐Metal Dichalcogenides. Issue 10 (16th April 2020) - Tang, Chi Sin; Yin, Xinmao; Yang, Ming; Wu, Di; Wu, Jing; Wong, Lai Mun; Li, Changjian; Tong, Shi Wun; Chang, Yung‐Huang; Ouyang, Fangping; Feng, Yuan Ping; Wang, Shi Jie; et al.
Abstract: The quasimetallic 1T′ phase 2D transition‐metal dichalcogenides (TMDs) consist of 1D zigzag metal chains stacked periodically along a single axis. This gives rise to its prominent physical properties which promises the onset of novel physical phenomena and applications. Here, the in‐plane electronic correlations are explored, and new mid‐infrared plasmon excitations in 1T′ phase monolayer WSe2 and MoS2 are observed using optical spectroscopies. Based on an extensive first‐principles study which analyzes the charge dynamics across multiple axes of the atomic‐layered systems, the collective charge excitations are found to disperse only along the direction perpendicular to the chains. Further analysis reveals that the interchain long‐range coupling is responsible for the coherent 1D charge dynamics and the spin–orbit coupling affects the plasmon frequency. Detailed investigation of these charge collective modes in 2D‐chained systems offers opportunities for novel device applications and has implications for the underlying mechanism that governs superconductivity in 2D TMD systems. Abstract : New 1D mid‐infrared anisotropic plasmons are observed in the quasimetallic phase of WSe2 and MoS2 monolayers. In‐depth analysis reveals that the long‐range inter‐chain coupling is responsible for this 1D charge dynamics, and the plasmon energy is dictated by the effects of spin–orbit coupling. This study establishes an inextricable link between the 1D‐chain structure and charge dynamics in quasimetallic phase 2D transition‐metal dichalcogenides.